PENGARUH LINGKUNGAN KERJA NON FISIK DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PELAYANAN PBB BADAN PENDAPATAN DAERAH KOTA TANGERANG SELATAN - Muhammad Yusron Fadlillah; Nindie Ellesia (Journal of Research and Publication Innovation, 2025)
This research aims to determine the influence of the Non-Physical Work Environment on Employee Performance, to determine the influence of Work Motivation on Employee Performance and to determine the Non-Physical Work Environment and Work Motivation on the Performance of PBB Service Employees at the South Tangerang City Regional Revenue Agency. Research methodology with quantitative methods. The sample used in this research was 50 respondents. The analytical methods used are simple linear regression test, multiple linear regression test, coefficient of determination, partial test (t test) and simultaneous test (f). The results of the research show that: 1) The Non-Physical Work Environment has a positive and significant effect on the Performance of PBB Service Employees of the Regional Revenue Agency of South Tangerang City as evidenced by the value of tcount 3.241 > ttable 2.011 with a significance of 0.000 < 0.05. 2) Work Motivation has a positive and significant effect on the performance of PBB Service Employees at the Regional Revenue Agency of South Tangerang City as evidenced by the tcount value of 4.694 > ttable 2.011 with a significance of 0.000 < 0.05. 3) Non-Physical Work Environment and Work Motivation have a positive and significant effect on the Performance of PBB Service Employees of the Regional Revenue Agency of South Tangerang City as evidenced by the fcount value of 11.593 > ftable 3.20 with a significance of 0.000< 0.05.